2011
DOI: 10.1021/mp100402n
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Active and Passive Targeting of Docetaxel for Prostate Cancer Therapy by HPMA Copolymer–RGDfK Conjugates

Abstract: N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-docetaxel-RGDfK conjugate was synthesized, characterized, and evaluated in vitro and in vivo in comparison with untargeted low and high molecular weight HPMA copolymer-docetaxel conjugates. The targeted conjugate was designed to have a hydrodynamic diameter below renal threshold to allow elimination post treatment. All conjugates demonstrated the ability to inhibit the growth of DU145 and PC3 human prostate cancer cells and the HUVEC at low nanomolar concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…High-affinity folate-binding protein was characterized in human hepatoma cell line SMMC-7721, and folic acid binds to the membrane fraction that cross reacts with the anti-intestines-specific membrane antigen antibody. Therefore, we firmly believed that the DTX-FA-HSANPs with smaller hydrodynamic size would have higher cellular uptake efficiency (Mi et al, 2011;Ray et al, 2011).…”
Section: In Vitro Cellular Uptakementioning
confidence: 96%
“…High-affinity folate-binding protein was characterized in human hepatoma cell line SMMC-7721, and folic acid binds to the membrane fraction that cross reacts with the anti-intestines-specific membrane antigen antibody. Therefore, we firmly believed that the DTX-FA-HSANPs with smaller hydrodynamic size would have higher cellular uptake efficiency (Mi et al, 2011;Ray et al, 2011).…”
Section: In Vitro Cellular Uptakementioning
confidence: 96%
“…For example HPMA copolymers containing cyclic Arg-GlyAsp peptides have been developed for targeting αvβ3 integrins expressed on angiogenic tumor blood vessels and other tumor cells. The anticancer and antiangiogenic agent, geldanamycin (aminohexylgeldanamycin), was conjugated to the polymer backbone through a lysosome-degradable GFLG (Gly-Phe-Leu-Gly) linker and the molecular weight was maintained at 40 kDa to ensure renal clearance after administration (112)(113)(114)(115)(116). The authors reported significantly higher localization of drug-loaded HPMA copolymer containing the arginylglycylaspartic acid (RGD) peptide (target moiety) in tumour cells and tumour growth suppression in prostate cancer bearing mice compared to control without a targeting moiety.…”
Section: Active Targetingmentioning
confidence: 99%
“…The RGD sequence, an arginine-glycine-aspartic (Arg-Gly-Asp) tripeptide, has been identified as a high affinity α v β 3 selective ligand (Ray et al, 2011). The α v β 3 , one of the integrin receptor family, is proved to be overexpressed on the angiogenic endothelium in malignant or diseased tissues (Temming et al, 2007;Barczyk et al, 2010), and it is also an important marker of blood vessels in the most malignant tumors, all of which make it an attractive target for antitumors strategy (Murphy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The α v β 3 , one of the integrin receptor family, is proved to be overexpressed on the angiogenic endothelium in malignant or diseased tissues (Temming et al, 2007;Barczyk et al, 2010), and it is also an important marker of blood vessels in the most malignant tumors, all of which make it an attractive target for antitumors strategy (Murphy et al, 2008). As a result, the conjugate modified with RGD demonstrates extraordinary potential to target drug to the tumors (Ray et al, 2011;Xu et al, 2012). In addition, the α v β 3 is also highly expressed in bone metastatic cells and osteoclasts, so that the α v β 3 integrin is also an attractive target for bone (Teti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%